Visualization of Electric Field Response for a Semi Circle Transmitter in Seabed Logging - Dahy, E. (Springer Science and Business Media Deutschland GmbH, 2022)
Sea bed logging (SBL) is a technique that makes use of remote application of the control source electromagnetic method (CSEM) to detect presence of an oil reservoir. In this technique, electromagnetic (EM) waves transmitted from a horizontal electric dipole (HED) are used to detectÂ the difference in resistivity between the different mediums. A curved electric dipole antenna (CED) is proposed as a new source of EM waves. This chapter presents a 3D visualization of electric field response of the CED. The results show that the CED has potential to be used for hydrocarbon exploration. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.